Retraction notice to âEnhanced gas separation performance using carbon membranes containing nanocrystalline cellulose and BTDA-TDI/MDI polyimideâ Chem. Eng. Res. Des. 140 (2018) 221â228 (Chemical Engineering Research and Design (2018) 140 (221â228), (S0263876218305173), (10.1016/j.cherd.2018.09.039)) - Sazali, N. (Institution of Chemical Engineers, 2020)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal). This article has been retracted after consideration by the Editor-in-Chief and subject specialists. Concerns were received regarding experimental data presented in this paper, for example in Figure 1, where there are inexplicable similarities between data shown, e.g. CM-700 with 2-cycles and CM-600 with 3-cycles. Concern was also raised with respect to Figure 3, the XRD analysis of polymeric and carbon membrane of PI at different carbonization temperature. The authors were provided an opportunity to respond which was again reviewed by the editorial team and subject specialists. It was concluded that the authors have not been able to provide reasonable explanations for the concerns raised and the Editorial team has decided to retract the article. The scientific community and this journal take a very strong view on the correctness of data produced in articles offered to readers of the journal. We accept that this similarity should have been detected during the submission process and will be reviewing our processes. Â© 2020 Institution of Chemical Engineers